Approaches for elucidating genetic susceptibility to SARS-CoV-2 - Baillie, Kenneth (Henry Stewart Talks, 2020)
Methodologies and sample acquisition for genetic studies, Current knowledge of genetic susceptibility to the virus, Future steps in the study, Possible implications of the acquired knowledge